2020
DOI: 10.1186/s12890-020-01237-0
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 specific serological pattern in healthcare workers of an Italian COVID-19 forefront hospital

Abstract: Background COVID-19 is an infectious disease caused by a novel coronavirus (SARS-CoV-2). The immunopathogenesis of the infection is currently unknown. Healthcare workers (HCWs) are at highest risk of infection and disease. Aim of the study was to assess the sero-prevalence of SARS-CoV-2 in an Italian cohort of HCWs exposed to COVID-19 patients. Methods A point-of-care lateral flow immunoassay (BioMedomics IgM-IgG Combined Antibody Rapid Test) was adopted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 9 publications
12
85
2
1
Order By: Relevance
“…These low overall infection rates are despite more than 170 patients with SARS-CoV-2 infections that had been treated at our center during the study period. Notwithstanding considerable exposure to COVID-19, infection rates in our study were substantially lower than in HCWs from Belgium (12.6%) ( Martin et al, 2020 ), Spain (11.2%) ( Garcia-Basteiro et al, 2020 ), Italy (14.4%) ( Sotgiu et al, 2020 ), Sweden (19.1%) ( Rudberg et al, 2020 ) the United Kingdom (10.8%–43.5%) ( Martin et al, 2020 ; Houlihan et al, 2020 ) and the United Stated of America (7.6%–13.7%) ( Moscola et al, 2020 ; Stubblefield et al, 2020 ). Those marked differences in infection rates may be partially explained by local differences in community transmission: population seroprevalence has been estimated to be 8.0% in Belgium, 5.5% in Spain, 4.6% in Italy, 3.7% in Sweden, 5.1% in the United Kingdom, and only 0.85% in Germany by May 2020 ( Flaxman et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…These low overall infection rates are despite more than 170 patients with SARS-CoV-2 infections that had been treated at our center during the study period. Notwithstanding considerable exposure to COVID-19, infection rates in our study were substantially lower than in HCWs from Belgium (12.6%) ( Martin et al, 2020 ), Spain (11.2%) ( Garcia-Basteiro et al, 2020 ), Italy (14.4%) ( Sotgiu et al, 2020 ), Sweden (19.1%) ( Rudberg et al, 2020 ) the United Kingdom (10.8%–43.5%) ( Martin et al, 2020 ; Houlihan et al, 2020 ) and the United Stated of America (7.6%–13.7%) ( Moscola et al, 2020 ; Stubblefield et al, 2020 ). Those marked differences in infection rates may be partially explained by local differences in community transmission: population seroprevalence has been estimated to be 8.0% in Belgium, 5.5% in Spain, 4.6% in Italy, 3.7% in Sweden, 5.1% in the United Kingdom, and only 0.85% in Germany by May 2020 ( Flaxman et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 66%
“…This approach is paramount to evaluate and adjust infection control measures to mitigate nosocomial transmission of SARS-CoV-2. By now, several studies have demonstrated high seroprevalence in HCWs in countries most affected by COVID-19 ( Garcia-Basteiro et al, 2020 ; Sotgiu et al, 2020 ; Rudberg et al, 2020 ; Houlihan et al, 2020 ; Martin et al, 2020 ; Moscola et al, 2020 ; Stubblefield et al, 2020 ) but data from German HCWs are scarce ( Korth et al, 2020 ). By 17th July 2020, a total of 5232 cases had been confirmed amongst the 1.9 million inhabitants of the city of Hamburg, which constituted one of the highest infection rates in Germany ( Robert Koch Institute, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This the approach adopted by our Occupational Health Unit during the so called “second wave” of the epidemics. A serologic retrospective study in in healthcare workers in our hospital revealed that individuals with IgM and IgG were 14.4 and 7.4%, respectively with no relationship was between exposure to Covid-19 patients and serological status ( 39 ).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 82%
“…A recent review article on asymptomatic COVID-19 transmission underlined this risk in the healthcare setting, although concentrating on the risk arising from asymptomatic patients [ 20 ]. A recent study has revealed that apparently healthy HCWs might have developed IgG and IgM antibodies, although no association with being exposed to COVID-19 patients was found [ 21 ]. These results indicate that relying on symptoms might not be an optimal strategy, and our results put the focus on source control.…”
Section: Discussionmentioning
confidence: 99%